ANALYSIS OF ASSERTIVE COMMUNICATION ON STATE CIVIL APPARATUS PERFORMANCE MEDIATED BY REWARD-BASED MOTIVATION - Setiawan, Angga; Supeno, Bambang; Yusuf, M. (PENANOMICS: International Journal of Economics, 2024)
In the era of globalization and the complexity of public services, the civil servants performance is one aspect that is highly considered. Good performance not only affects administrative efficiency but also public satisfaction with the services provided. Therefore, an approach that can improve civil servants performance needs to be implemented, one of which is through assertive communication. Assertive communication refers to an individual's ability to express opinions and needs in a clear, direct, and respectful manner. This is due to various things, including assertive communication, civil servant performance, and reward-based motivation. That's why this study looked at how assertive communication affects reward-based motivation, how assertive communication affects the work of civil servants performance, how reward-based motivation affects the work of civil servants performance, and how assertive communication through reward-based motivation affects the work of civil servants performance. The research method is quantitative with descriptive explanations; this study used a sample of 59 civil servants and data processing using SEM PLS. The research findings show that 1) assertive communication has a positive effect on reward-based motivation. 2) Assertive communication does not affect the civil servants performance. 3) Reward-based motivation has a positive effect on the civil servants performance. 4) Assertive communication through reward-based motivation affects the civil servants performance